Hubungan Usia Ibu dan Peran Suami dengan Pemilihan Metode Kontrasepsi Hormonal pada Pasangan Usia Subur - Heny Ekawati; Wahyu Retno Gumelar; Suhariyati Suhariyati; Surya Prayoga; Risky Asta Pramestirini (Journal of Telenursing (JOTING), 2023)
The purpose of this study was to determine the relationship between maternal age and husband's role in relation to the choice of hormonal contraceptive methods for couples of childbearing age in the working area of the Baureno Health Center, Bojonegoro Regency. This research method is analytic correlation with a cross-sectional approach. Samples were taken using the Simple Random Sampling technique. The results showed that more than a quarter of mothers (37.5%) were between 17 and 25 years old, the majority of husbands (57.%) played a positive role, and almost half of mothers (41.7%) chose the 28-day birth control pill. Using the contingency coefficient test, it was found that there was a relationship between maternal age and the choice of hormonal contraception method in couples of childbearing age (p=0.035), but there was no relationship between the husband's role and the choice of hormonal contraception method in these couples (p=0.266). In conclusion, there is a relationship between maternal age and the choice of hormonal contraceptive methods at childbearing age. Keywords: Hormonal Contraception, Husband's Role, Mother's Age